Silk fibroin-sodium dodecyl sulfate gelation: molecular, structural, and rheological insights - Hirlekar, Swarali; Ray, Debes; Aswal, Vinod K.; Prabhune, Asmita; Nisal, Anuya; Ravindranathan, Sapna (Langmuir, 2019)
A gelling agent is necessary to accelerate sol to gel transition in an aqueous solution of silk fibroin (SF), which otherwise takes several days to complete. In this paper, we investigate the mechanism of gelation of Bornbyx mori SF by a model anionic surfactant, sodium dodecyl sulfate (SOS). Even though interactions between SDS and proteins have been extensively investigated, most of these studies have focused on globular proteins, which undergo denaturation. The interaction with a fibrous protein such as SF is different and results in an altered secondary structure leading to gelation. In this work, the concentration-dependent gelation process of the SF-SDS system is examined using rheology, SANS, FTIR, and NMR. We observed preferential binding of SDS to specific regions on the SF chain, which aids structural changes favoring beta-sheet formation. We propose a mechanism for the accelerated sol-gel transition in the SF-SDS system.

Lauric acid sophorolipid: accelerating the gelation of silk fibroin - Hirlekar, Swarali; Ray, Debes; Aswal, Vinod K.; Prabhune, Asmita A.; Nisal, Anuya (ACS Omega, 2020)
Silk fibroin (SF) hydrogels find wide applications in tissue engineering. However, their scope has been limited due to the long gelation time in ambient conditions. This paper shows the reduction in gelation time of silk fibroin to minutes upon doping with a newly synthesized lauric acid sophorolipid (LASL). LASL comprises a fatty acid, lauric acid (with a 12-carbon aliphatic chain), that is derivatized by glucose molecules using a non-pathogenic yeast Candida bombicola. LASL was characterized using spectroscopic (Fourier transform infrared spectroscopy) and chromatographic (high-performance liquid chromatography, thin-layer chromatography, and high-resolution mass spectrometry) methods. This gelation of SF is comparable to the effect of an anionic surfactant, sodium dodecyl sulfate (SDS). The microstructure of SF-LASL hydrogels was investigated by small-angle neutron scattering (SANS) measurements and exhibited the beads-on-a-necklace model. The rheological properties of these hydrogels show similarity to SF-SDS hydrogels, therefore presenting a greener alternative for tissue engineering applications.

Green antibacterial molecules: sophorolipids with varying fatty acid chain - Hirlekar, Swarali; Abhyankar, Isha; Kane, Kartiki; Trimukhe, Kalpana; Prabhune, Asmita; Nisal, Anuya (Trends in Biomaterials and Artificial Organs, 2021)
Antibiotic resistance is a rising problem of over the last decade making it difficult to treat infections caused by various pathogenic bacteria. To tackle this problem, newer antimicrobial strategies are being explored. Sophorolipids (SLs) are a class of biomolecules produced by a non-pathogenic yeast Starmarella bombicola (S. bombicold) with surfactant as well as potent broad spectrum antibacterial activity. In this work, we have successfully synthesized sophorolipids using different fatty acids with increasing chain length of hydrophobic tail; Lauric acid (C12)-LASL, Myristic acid (C14)-MASL, Palmitic acid (C16)-PASL and Stearic acid (C18)-SASL. We have used various techniques like FTIR, HRMS to characterize the synthesized SL. Further, we have measured properties like the critical micellar concentration for these biosurfactants and the SL's showed CMC less than or equal to 100 mg/L indicating excellent surface-active property. We have studied the antibacterial activity against gram-negative and gram-positive bacteria. Interestingly, the antibacterial activity was found to be more potent as the chain length of the fatty acid in the SL decreased. This trend was found to be reverse for toxicity towards mammalian cells. The shorter chain fatty acid SL's were found to be less cytotoxic. These results indicate that the sophorolipid candidates with shorter chain lengths would be beneficial for various biomedical applications such as tissue engineering, regenerative medicine and wound healing. Keywords: sophorolipid, biosurfactant, short chain fatty acid, antibacterial
Keywords: Antibacterial agents; Cells (Biology); Infection; Microbial drug resistance; Saturated fatty acids; Surface active agents

Bridging the gap: an investigation of biosurfactants-polymer systems - Abhyankar, Isha; Hirlekar, Swarali; Prabhune, Asmita; Nisal, Anuya (Current Opinion in Colloid & Interface Science, 2024)
Biosurfactants (BSs) have been extensively researched due to their potential applications in various fields, including textiles, cosmetics, pharmaceuticals, agriculture, and oil remediation. These BSs possess a diverse range of physical, chemical, and biological properties. In recent years, researchers have combined these biosurfactants with both natural and synthetic polymers, resulting in the development of advanced material systems that exhibit a unique combination of properties. This review focuses on highlighting the recent advancements in these biosurfactant-polymer material systems and identifies existing gaps in the literature. The combination of biosurfactants with polymers has led to the formation of interpenetrated hydrogels, films, chemically modified surfaces, vesicles, functionalized nanofiber nonwoven mats, nano-formulations, and nano-assemblies. Some studies have also investigated the interactions between biosurfactants and polymer molecules. In most cases, non-specific, non-covalent interactions, such as electrostatic interactions, hydrogen bonding, and hydrophobic interactions have been found to govern the properties of these systems. Moreover, promising results have been achieved through the covalent modification of polymer surfaces, followed by functionalization using biosurfactant molecules. The literature demonstrates that these advanced materials could find applications in various fields, including drug delivery, bioremediation, biomedical materials, and as antimicrobial agents. These findings indicate the promising potential of biosurfactant-polymer systems for future advancements in these areas.